Cold snare polypectomy for large sessile serrated lesions is safe but follow‐up is needed: a single‐centre retrospective study. Issue 3 (10th February 2021) - Yoshida, Naohisa; Inoue, Ken; Tomita, Yuri; Hashimoto, Hikaru; Sugino, Satoshi; Hirose, Ryohei; Dohi, Osamu; Naito, Yuji; Morinaga, Yukiko; Kishimoto, Mitsuo; Inada, Yutaka; Murakami, Takaaki; et al.
Abstract: Background and Aim: Cold snare polypectomy (CSP) is growing in popularity due to its safety and convenience. Its indication is benign tumours such as adenoma and sessile serrated lesions (SSLs) <10 mm in size. CSP for SSLs ≥10 mm in size has not been well examined. In this study, we aimed the feasibility of this treatment regarding therapeutic results and local recurrence. Methods: This was a single‐centre retrospective cohort study. We reviewed SSLs with or without dysplasia of 10–20 mm that were resected by CSP from 2014 to 2020. All tumours were diagnosed endoscopically as SSLs without dysplasia before CSP with the help of magnifying narrow band imaging or blue laser imaging. We analysed the lesion characteristics, en bloc resection, histopathological diagnosis, adverse events and local recurrence. We analysed risk factors for recurrence, comparing recurrent lesions to non‐recurrent lesions. We also compared risk factors for lesions 10–14 mm in size to those for lesions 15–20 mm in size. Results: We analysed 160 lesions in 100 patients ( M age  ±  SD  = 67.7 ± 10.1 years). The polyp size ( M  ±  SD ) was 11.8 ± 2.8 mm, and the en bloc resection rate was 60.0% (96 cases). The rates of massive perioperative haemorrhage, postoperative haemorrhage and perforation were 1.3%, 0% and 0%, respectively. Regarding histopathological diagnosis, two (1.2%) cases showed SSLs with high‐grade dysplasia. The recurrence rate in 101 lesions with a median follow‐up period of 18 months (interquartile range 12–24 months) was 5.0%. There were no significant risk factors such as tumour size, location, morphology and so on in terms of recurrence. All recurrent cases could be resected by repeat CSP. The recurrence rates of lesions 10–14 mm in size and 15–20 mm in size were 4.7% and 6.3%, respectively ( p  = 0.713). Conclusion: CSP of SSLs ≥10 mm in size according to magnifying endoscopic diagnosis was safe and promising, but the rate of recurrence was slightly high, meaning that close follow‐up is required.